Systemic treatment with or without ablative therapies in oligometastatic breast cancer: A single institution analysis of patient outcomes. (February 2023) - Glemarec, Gauthier; Lacaze, Jean-Louis; Cabarrou, Bastien; Aziza, Richard; Jouve, Eva; Zerdoud, Slimane; De Maio, Eleonora; Massabeau, Carole; Loo, Maxime; Esteyrie, Vincent; Ung, Mony; Dalenc, Florence; et al.
Abstract: Purpose: Local ablative treatment (LAT) is increasingly combined with systemic therapy in oligometastatic breast cancer (OMBC), without a high-level evidence to support this strategy. We evaluated the addition of LAT to systemic treatment in terms of progression-free survival (PFS) and overall survival (OS). Secondary endpoints were local control (LC) and toxicity. We sought to identify prognostic factors associated with longer OS and PFS. Methods and materials: We identified consecutive patients treated between 2014 and 2018 for synchronous or metachronous OMBC (defined as ≤ 5 metastases). LAT included stereotactic body radiation therapy (SBRT) and volumetric modulated arc therapy (VMAT), surgery, cryotherapy and percutaneous radiofrequency ablation (PRA). PFS and OS were calculated, and Cox regression models analyzed for potential predictors of survival. Results: One hundred two patients were included (no-LAT, n = 62; LAT, n = 40). Sixty-four metastases received LAT. Median follow-up was 50.4 months (95% CI [44.4; 53.4]). One patient experienced grade 3 toxicity in the LAT group. Five-year PFS and OS were 34.75% (95% CI [24.42–45.26]) and 63.21% (95% CI [50.69–73.37]) respectively. Patients receiving both LAT and systemic therapy had longer PFS and OS than those with no-LAT ([HR 0.39, p = 0.002]) and ([HR 0.31, p = 0.01]). The use of LAT, HER2-positive status and hormone-receptor positivity were associated with longer PFS and OS whereas liver metastases led to worse PFS. Conclusions: LAT was associated with improved outcomes in OMBC when added to systemic treatment, without significantly increasing toxicity. The prognostic factors identified to extend PFS and OS may help guide clinicians in selecting patients for LAT. Highlights: Outcomes of oligometastatic breast cancer (OMBC) cohort without cranial metastatases treated by local ablative treatment and systemic treatment. Patients with LAT had more favorable PFS and OS compared to noLAT. HR+ and HER + immunohistochemical (HIC) subtype had a more favorable OS and PFS compared to triple negatives patients, liver metastases had a worse PFS.